Incidence of Helicobacter pylori infection using (13) C- urea breathtest and gastric biopsy culture - Jaafar, Khairul Azhar; Sheikh Omar, Sheikh Anwar Abdullah; Razlan, Hamizah; Mohamed, Ramelah (Faculty of Medicine, International Islamic University Malaysia, 2007)
(13) C – urea breath test (UBT) is sensitive and specific for detection of Helicobacter pylori (H. pylori) infection. Gastric biopsy culture for H. pylori confirms the diagnosis. Here, we analyzed data of all patients who were investigated for H. pylori infection using both tests throughout the year 2005.